2014
DOI: 10.1002/2014gc005377
|View full text |Cite
|
Sign up to set email alerts
|

Ferro and antiferromagnetism of ultrafine‐grained hematite

Abstract: Aluminum-substituted hematite (here referred to as Al-Hm) is an important magnetic mineral for paleo and environmental magnetism. However, the magnetic properties of nanosized Al-Hm are poorly known. In this study, a series of Al-Hm samples (fourteen samples) and their nonsubstituted counterparts (referred to as pure-Hm) (seven samples) were synthesized with particle sizes ranging from 14 to 124 nm. With decreasing particle size, coercive force (B c ), magnetic remanence (M r ) acquired in a 5 T field at room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…Defects resulting from Al incorporation inhibit magnetic domain rotation and flipping, which causes an increase in magnetic hardness. The coercivity of hematite also increases with grain size in the SD size range [ Jiang et al ., , ; Özdemir and Dunlop , ]. Özdemir and Dunlop [] demonstrated that the traditional HIRM (1 T, −300 mT) parameter is only sensitive to hematite particles with sizes from ~0.3 to 3 µm, which is consistent with results for HFh8 (Figure a).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Defects resulting from Al incorporation inhibit magnetic domain rotation and flipping, which causes an increase in magnetic hardness. The coercivity of hematite also increases with grain size in the SD size range [ Jiang et al ., , ; Özdemir and Dunlop , ]. Özdemir and Dunlop [] demonstrated that the traditional HIRM (1 T, −300 mT) parameter is only sensitive to hematite particles with sizes from ~0.3 to 3 µm, which is consistent with results for HFh8 (Figure a).…”
Section: Resultssupporting
confidence: 77%
“…The ubiquity of Al in weathering environments results in most Fe oxides in soils being Al substituted [ Cornell and Schwertmann , ; Fontes and Weed , ; Friedl and Schwertmann , ; Wiriyakitnateekul et al ., ]. According to previous studies and results presented here, Al substitution affects both DRS and magnetic properties [ Dekkers , ; Dekkers and Linssen , ; Jiang et al ., , ; Liu et al ., ; Malengreau et al ., ; Torrent and Barrón , ], such as HIRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not unusual for the Morin transition to be suppressed in natural hematite due to poor crystallinity, cation-substitution, or nanoparticle effects (Vandenberghe et al, 2001;Maher et al, 2004;Özdemir et al, 2008;Jiang et al, 2014).…”
Section: Low-temperature Magnetic Properties: Goethite and Hematitementioning
confidence: 99%
“…The magnetic properties of Hematite nanocrystals are a topic of interest as well [16][17][18] because crystalline α-Fe 2 O 3 has the characteristics of an antiferromagnet below the Morin temperature T M . When the temperature is above T M , it exhibits weakly parasitic ferromagnetic properties [19].…”
Section: Introductionmentioning
confidence: 99%